Physical activity, screen time and the COVID-19 school closures in Europe – An observational study in 10 countries. Issue 7 (3rd July 2022) - Kovacs, Viktoria A.; Starc, Gregor; Brandes, Mirko; Kaj, Monika; Blagus, Rok; Leskošek, Bojan; Suesse, Thomas; Dinya, Elek; Guinhouya, Benjamin C.; Zito, Viviana; Rocha, Paulo M.; Gonzalez, Benito Perez; et al.
ABSTRACT: To date, few data on how the COVID-19 pandemic and restrictions affected children's physical activity in Europe have been published. This study examined the prevalence and correlates of physical activity and screen time from a large sample of European children during the COVID-19 pandemic to inform strategies and provide adequate mitigation measures. An online survey was conducted using convenience sampling from 15 May to 22 June, 2020. Parents were eligible if they resided in one of the survey countries and their children aged 6–18 years. 8395 children were included (median age [IQR], 13 [10–15] years; 47% boys; 57.6% urban residents; 15.5% in self-isolation). Approximately two-thirds followed structured routines (66.4% [95%CI, 65.4–67.4]), and more than half were active during online P.E. (56.6% [95%CI, 55.5–57.6]). 19.0% (95%CI, 18.2–19.9) met the WHO Global physical activity recommendation. Total screen time in excess of 2 h/day was highly prevalent (weekdays: 69.5% [95%CI, 68.5–70.5]; weekend: 63.8% [95%CI, 62.7–64.8]). Playing outdoors more than 2 h/day, following a daily routine and being active in online P.E. increased the odds of healthy levels of physical activity and screen time, particularly in mildly affected countries. In severely affected countries, online P.E. contributed most to meet screen time recommendation, whereas outdoor play was most important for adequate physical activity. Promoting safe and responsible outdoor activities, safeguarding P.E. lessons during distance learning and setting pre-planned, consistent daily routines are important in helping children maintain healthy active lifestyle in pandemic situation. These factors should be prioritised by policymakers, schools and parents. Highlights: To our knowledge, our data provide the first multi-national estimates on physical activity and total screen time in European children roughly two months after COVID-19 was declared a global pandemic. Only 1 in 5 children met the WHO Global physical activity recommendations. Under pandemic conditions, parents should set pre-planned, consistent daily routines and integrate at least 2-hours outdoor activities into the daily schedule, preferable on each day. Schools should make P.E. lessons a priority. Decision makers should mandate online P.E. be delivered by schools during distance learning. Closing outdoor facilities for PA should be considered only as the last resort during lockdowns.